The Influence of Talent Management and Retention on Employee Performance at the Dhinda Hijab Store - heri hermansyah,; Sari Marliani,; July Yuliawati,; Uus Mohammad Darul Fadli, (Research in Management of Technology and Business, 2024)
MSDM encompasses a variety of activities in a company that aims to recruit, retain, and improve performance to stay at its best to achieve its desired goals. Human resources are the main capital in a company. This researcher aims to be able to find out the influence of talent management and employee retention on employee performance at Dhinda Hijab Store. This study uses a quantitative method with a descriptive-verifiable approach and uses SPSS v27. The research respondents consisted of 57 employees who were a sample from Dhinda Hijab Store. The analysis was carried out using descriptive methods and multiple linear regression. The results of the descriptive analysis show that talent management (X1), employee retention (X2), and employee performance (Y) all meet the criteria of "good". The results of the t-test show that: The talent management variable (X1) has no significant effect on employee performance (Y). The employee retention variable (X2) has a significant partial effect on employee performance (Y). The F test simultaneously showed that the variables of employee retention and talent management had a significant effect on employee performance (Y).